Hermite–Hadamard and Fractional Integral Inequalities for Interval-Valued Generalized p-Convex Function. (21st October 2020) - Li, Zhengbo; Kamran,; Zahoor, Muhammad Sajid; Akhtar, Huma
Abstract : In the present paper, the new interval-valued generalized p convex functions are introduced. By using the notion of interval-valued generalized p convex functions and some auxiliary results of interval analysis, new Hermite–Hadamard and Fejér type inequalities are proved. The established results are more generalized than existing results in the literature. Moreover, fractional integral inequality for this generalization is also established.